Postharvest application of phosphites reduces blue mold on 'FUJI' and 'GALA' apples Fosfitos aplicados em pós-colheita reduzem o mofo-azul em maçãs 'FUJI' e 'GALA' - Blum L.E.B. (2007)
Blue mold (Penicillium expansum) is a common postharvest disease of apples (Malus domestica). Applications of less hazardous substances to the environment, such as phosphite (phosphonic acid), is an alternative to the control of blue mold. The main goal of this study was to evaluate the efficiency of phosphite-K (40% P2O5 and 30% K2O) and phosphite-CaB (10.7% P2O5, 3.89% Ca, and 0.5% B) for the control of blue mold on 'Fuji' and 'Gala' apples. Tests were designed in randomized blocks with six replications of 20 fruits. Fruits were decontaminated with Na hypochlorite (1%) for three minutes, washed with sterilized water, needle wounded (with a diameter and deepness of 1mm) in four equidistant points, dipped into treatments for 15 minutes, and then stored at 15-20°C. The following substances were added in suspensions contaminated with Penicillium expansum (at the concentration of 1 × 102 conidia.mL-1): benomyl (at 150 mg.L -1), phosphite-K (from 0.5 to 1.5 mL.L-1) and phosphite-CaB (from 1.5 to 3.0 mL.L-1). 'Fuji' and 'Gala' apples dipped in water with phosphite-CaB (1.5 mL.L-1), phosphite-K (0.5-1.5 mL.L-1) or benomyl (150 mg.L-1) were less affected by the blue mold. Application of phosphite-K (1.5 mL.L-1) or benomyl were the most effective treatments to control the disease.